Modesty as Kindness. (12th January 2014) - Wilson, Alan T.
Abstract: The trait of modesty has received significant philosophical attention in recent years. This is due, in part, to Julia Driver's claim that modesty is able to act as a counter‐example to intellectualist accounts of the nature of virtue. In this paper I engage with the debate about the nature of modesty by proposing a new account. 'Modesty as kindness' states that the trait of modesty ought to be considered as intimately connected with the more fundamental virtue of kindness. I set out the account, explain its benefits and defend it against possible objections. I then ask whether or not the intense focus on the trait of modesty has actually furthered our understanding of the nature of virtue more generally, and suggest that alternative approaches ought to be considered.